Exploring Scientific Inquiry Literacy Among Physics Teachers - Shintya, Rizki Eka; Harahap, Syafnah Aisyah Nauli; Suhandi, Andi; Sari, Ika Mustika (FKIP Universitas Lampung, 2025)
This study aims to examine the Scientific Inquiry Literacy (SIL) of in-service physics teachers in West Java. focusing on three key aspects: knowledge. skills. and attitudes toward scientific inquiry. The research addresses the need to understand teachers' readiness to implement inquiry-based instruction as part of quality science education. A descriptive survey design was employed involving 27 physics teachers from various cities and regencies in West Java. Participants were selected through purposive sampling based on their active teaching status and academic background. Data were collected via an online questionnaire using the Scientific Inquiry Literacy Instrument (SILI). which comprises 35 multiple-choice items on knowledge. 39 on skills. and 30 attitude statements. Rasch Model analysis was applied to evaluate person and item measures. reliability. and item difficulty. with Wright Map outputs used to visualize the distribution of teacher abilities. Results showed that the overall SIL of participating teachers was relatively high. as indicated by a mean person measure above the item mean across all aspects. Among the three aspects. the attitude aspect (AA) yielded the highest person measure (1.57). followed by knowledge (KA) at 0.50 and skills (SA) at 0.13. Despite these strengths. the data revealed a mismatch between teacher ability and item difficulty in some areas. suggesting a potential ceiling effect and room for improvement. particularly in applying complex inquiry skills. While physics teachers in this study demonstrate a generally strong level of scientific inquiry literacy. the use of non-probability sampling and a small sample size limits the generalizability of the findings. Targeted professional development is recommended to strengthen teachers’ competencies in complex inquiry practices and to support the continued integration of inquiry-based learning in physics classrooms. Keywords: scientific inquiry literacy. inquiry-based learning. physics teachers.